Figureheads and Symbolism Between the Medieval and the Modern: The ship Griffin or Gribshunden, one of the last Sea Serpents?. Issue 3 (2nd July 2020) - Eriksson, Niklas
Abstract : The Griffin or, as it was sometimes called, Gribshunden (griffin hound) was a ship that belonged to the Danish–Norwegian King Hans. The ship sank in 1495 and was one of the largest and most modern warships of its day. In 2015 a peculiar figurehead carving was raised from the wreck. It is shaped like a beast swallowing a man screaming in agony. The question is, what this sculpture is meant to symbolize? This article aims to shed light on the enquiry through placing the sculpture in a wider chronological context. Against the background of a general overview, from the dragon heads of the late Iron Age to early modern figureheads, it is argued that the sculpture raised from the Griffin was carved in a period when figureheads did not relate to the ship's name or owner, but that the monstrous head is an expression of the spirit or character of the vessel.